INCOME AND ITS MEASUREMENT. - Crandell, William T. (The Accounting Review, 1935)
Some concept of income holds a prominent place in the consciousness of every individual. The very essence of economic activity is that of earning and enjoying income. As in the case, however, of many other terms of universal usage both in science and in business, the various concepts involved are confused and often conflicting. Even as a term used in technical economics, the definitions of income found in the writings of the leading authorities show pronounced differences of opinion. Income may be defined as the gain derived from capital, from labor, or from both combined, provided it be understood to include profit gained through the sale or conversion of capital assets. Net individual income is the flow of commodities and services accruing to an individual through a period of time and available for disposition after deducting the necessary cost of acquisition. Income in the broad sense all wealth which flows in to the taxpayer other than as a mere return of capital. Income or profit of a given period may be defined as the increase in proprietorship which has taken place during that period, making due allowances for any part of such increment as may have been distributed.